Minimizing river pollution by batik dye wastewater using palm oil fuel ash (POFA) as an environmentally friendly, low-cost adsorbent alternative - Ahmad Riduan; Rainiyati Rainiyati; Sarah Fiebrina Heraningsih; Badariah Badariah (Brawijaya University, 2022)
The rise of the batik industry in Jambi Province causes the accumulation of waste in the environment. Disposal of batik dye wastewater directly into the environment is one source of heavy metals entering the river. Palm Oil Fuel Ash (POFA), as a part of waste originating from combustion residues of oil palm, is potential to be used as a low-cost adsorbent in overcoming the batik dye wastewater problem. The POFA is also potential to be used in the removal of heavy metals and chemical and organic compounds in industrial waste treatment. This paper reported the potential use of POFA and the modification of POFA as batik dye adsorbents in overcoming waste problems from the batik industry. Results of this study showed that POFA could adsorb the dye in batik waste with up to 22% removal efficiency and adsorption capacity up to 62 mg/g. The isotherm adsorption in this study was in accordance with the Freundlich model that showed adsorption occurred at multi-layer and heterogeneous surfaces. The adsorption process occurred endothermically and spontaneously.